Beyond a phenomenological description of magnetostriction - A. H. Reid (Nature Portfolio, 2018)
Although magnetostriction is universal in magnetic materials, understanding its microscopic origin remains challenging. Here the authors use X-ray and ultrafast electron diffraction to separate the material’s sub-picosecond spin and lattice responses and reveal the magnetoelastic stress generated by demagnetization.